2015
DOI: 10.1155/2015/913470
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Controlled Irrigation and Drainage for Reducing Nitrogen Emission from Rice Paddies in Southern China

Abstract: The effect of controlled irrigation and drainage (CID) at different growth stages of rice on nitrogen (N) from rice paddy was studied. Submergence at different stages was imposed in specially designed experimental tanks in 2009 and 2010 based on alternate wetting and drying technology (AWD, the control, CK). Treatments include CID treatment at tiller stage (T1), jointing-booting stage (T2), panicle initiation stage (T3), and milky stage (T4). Results showed that fertilization could significantly increase the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Yang et al reported that straw return significantly increased the N uptake of rice plant [35], which may be a cause of the low concentration value of DP-SM. In general, NH4 + -N is less likely to leach than NO3 − -N as a result of the high soil adsorption the short migration distance of NH4 + -N [44,46]. However, the large amount of residual NH4 + -N would be rapidly lost when the soil absorption of NH4 + -N becomes saturated.…”
Section: The Variation Of Nh 4 + -N Concentration In Percolation Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al reported that straw return significantly increased the N uptake of rice plant [35], which may be a cause of the low concentration value of DP-SM. In general, NH4 + -N is less likely to leach than NO3 − -N as a result of the high soil adsorption the short migration distance of NH4 + -N [44,46]. However, the large amount of residual NH4 + -N would be rapidly lost when the soil absorption of NH4 + -N becomes saturated.…”
Section: The Variation Of Nh 4 + -N Concentration In Percolation Watermentioning
confidence: 99%
“…Peak values of 1.51 mg/L for FI, 1.15 mg/L for DP-SM were observed three days after the panicle fertilizer application. In general, NH 4 + -N is less likely to leach than NO 3 − -N as a result of the high soil adsorption the short migration distance of NH 4 + -N [44,46]. However, the large amount of residual NH 4 + -N would be rapidly lost when the soil absorption of NH 4 + -N becomes saturated.…”
Section: The Variation Of No3 − -N Concentration In Percolation Watermentioning
confidence: 99%
“…This is consistent with the work done by Shao et al . () on controlled irrigation and drainage at different crop stages where they found that nitrate and ammonia nitrogen losses decreased significantly in surface runoff.…”
Section: Resultsmentioning
confidence: 99%
“…The rice season in southern China coincides with the summer wet season, and average annual precipitation is approximately 500-1,000 mm. Drainage is an important measure to allow timely field operation and protect field rice from waterlogging [2]. Nitrogen (N) and phosphorus (P) loads from unmanaged agricultural non-point sources, such as runoff and leaching from paddy fields, are associated with water body eutrophication of many lakes and streams [3][4][5].…”
Section: Introductionmentioning
confidence: 99%